Aspects of the Topology and Combinatorics of Higgs Bundle Moduli Spaces - Rayan, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
This survey provides an introduction to basic questions and techniques surrounding the topology of the moduli space of stable Higgs bundles on a Riemann surface. Through examples, we demonstrate how the structure of the cohomology ring of the moduli space leads to interesting questions of a combinatorial nature.